Initial Results of Antegrade Laser Fenestrations Using Image Fusion Guidance and Company Manufactured Stent Grafts in Complex Aortic Aneurysm Repair. (August 2021) - Sénémaud, Jean; Fadel, Guillaume; Touma, Joseph; Tacher, Vania; Majewski, Marek; Cochennec, Frédéric; Kobeiter, Hicham; Desgranges, Pascal
Abstract : Objective: The aim was to describe initial outcomes of physician modified stent grafts using antegrade laser fenestrations and image fusion guidance (LEVAR) and company manufactured custom made (CM) stent grafts for the treatment of complex abdominal aortic aneurysms (CAAAs), thoraco-abdominal aortic aneurysms (TAAAs) and type I endoleaks (T1ELs). Methods: This was a retrospective single centre study. All LEVAR and Zenith (Cook) CM stent graft procedures between 1 January 2012 and 31 December 2018 were reviewed. Endpoints included intra-operative adverse events (IOAEs), in hospital mortality, re-interventions, target vessel patency, and 12 month outcomes (overall survival, freedom from re-intervention, target vessel patency). Outcomes at 12 months were estimated using the Kaplan–Meier method. Results: A hundred patients were identified and included in the study. All patients were deemed unfit for open repair. The cohort included 22 LEVAR and 78 CM stent grafts. LEVAR cases included painful aneurysms ( n = 5), > 65 mm aneurysms ( n = 10), anatomical constrains and/or presence of previous renal stents ( n = 7) or cases declined by the manufacturer planning centre ( n = 2). IOAEs were recorded in 41% of cases ( n = 9) in the LEVAR group vs. 10% ( n = 8, p = .002) in the CM group. The in hospital mortality rate in the LEVAR group was 9% ( n = 2) vs. 4% ( n = 3, p = .30) in the CM group. The median follow up duration was 22 months (7 – 38) in the LEVAR group and 28 months (11 – 78) in the CM group. The estimate of overall survival at one year was 91% in both groups. The freedom from re-intervention rate at one year was 58% in the LEVAR group vs. 87% in the CM group. The target vessel patency rates at one year were 95% in both groups. Conclusion: In high risk patients deemed unfit for open repair, LEVAR may provide satisfactory 12 month overall survival and target vessel patency rates, though reported IOAE, mortality, and re-interventions rates were high thus requiring close and extensive follow up.